Denis Diderot - Flashes of a biography - Ricardo, Marinêz de Fátima (Lettres Françaises, 2009)
The life and work of Denis Diderot, philosopher and French writer of the 18th century, is, unfortunately, not very well-known in Brazil. The studies that prevail among us are mainly about his philosophical contribution mainly in the movement called The Lights. However, Diderot wasn't limited to philosophy, whereas his studies and writings have approached several science, literature and art areas. In literature, he was devoted to novels and plays, in which he portrayed the society where he lived, but the way the themes were treated, and the structure used concerning the organization of his writings, facilitate a contemporary reading. Due to the extension of Diderot's biography, we just gathered information possible to have his importance outlined in French literature, in a brief study on that writer, considered for several theoreticals as one of the founders of the modern novel gender.